Adoption of B2B procurement services : a case of Singapore - Chua, Geck Leng. (2008)
The study focuses on Business-to-Business (B2B) procurement services (P.S.) that are used by organizations in Singapore. Included in this dissertation are the presentations on the eight basic models of B2B procurement services, five successful examples from literature research on companies that had used B2B procurement models to reap savings in costs and an interview with the General Manager of a local B2B service provider to gain more insights to the industry.